Effect of aromatic additives with various alkyl groups on orientation birefringence of cellulose acetate propionate. Issue 5 (23rd June 2013) - Nobukawa, Shogo; Aoki, Yoshihiko; Yoshimura, Hiroshi; Tachikawa, Yutaka; Yamaguchi, Masayuki
ABSTRACT Orientation birefringence and its wavelength dispersion in blends of cellulose acetate propionate (CAP) and aromatic additive molecules having various alkyl chains were investigated, in order to evaluate the effect of the chemical structure on the optical properties. We found that the additive improved the orientation birefringence of CAP, meaning that the additive orientation is parallel to CAP chains via the "nematic interaction (NI)" reflecting the intermolecular orientation correlation. The NI strength was evaluated by using a theory concerning the molecular orientation. The result demonstrates that the alkyl chain length in the additive molecule strongly affects the orientation correlation. Although the intrinsic birefringence monotonically decreases with the alkyl chain length, the NI strength shows the highest value between the additive with propionyl group and CAP. From the result, the contribution of birefringence from the aromatic molecule, which is determined by the intrinsic birefringence and orientation function, needs to be considered to design the optical films with high performances. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 3465–3472, 2013